If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying v + 4(-6 + 8v) = -24 + -4v v + (-6 * 4 + 8v * 4) = -24 + -4v v + (-24 + 32v) = -24 + -4v Reorder the terms: -24 + v + 32v = -24 + -4v Combine like terms: v + 32v = 33v -24 + 33v = -24 + -4v Add '24' to each side of the equation. -24 + 24 + 33v = -24 + 24 + -4v Combine like terms: -24 + 24 = 0 0 + 33v = -24 + 24 + -4v 33v = -24 + 24 + -4v Combine like terms: -24 + 24 = 0 33v = 0 + -4v 33v = -4v Solving 33v = -4v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '4v' to each side of the equation. 33v + 4v = -4v + 4v Combine like terms: 33v + 4v = 37v 37v = -4v + 4v Combine like terms: -4v + 4v = 0 37v = 0 Divide each side by '37'. v = 0 Simplifying v = 0
| 3.5x-7.5y=87 | | F(5)=2x+8 | | 3n-n=2 | | -12(b-12)=324 | | -5r^2+26r+24=0 | | v+2-4=4 | | log[5](x+18)+log[5](x-2)=3 | | 45x-180=720 | | 7=2x^2+4x+4-3 | | 5x-3x=12x+8 | | 5x-(x+2)=22 | | 6(y+3)+4y=13 | | 4x-5forx=6 | | -3(4+n)=-48 | | 2(5-2v)=-5(v-5) | | p(-p+6)=0 | | 15y-10(y+7)=-55 | | 6=8-7n+8n | | -(-6-7m)=5m-7(-3-1m) | | 2x-5+(x-1)=3x+6 | | 15t+10t^2=0 | | 6x-8+3x=5+9x-13 | | -16-5v=4v-7v | | -4p+3+4=-17 | | 12b+6b^2=0 | | -2(2f-4)=-5(-f+2) | | 73=25+4x | | 6n+1+4=11 | | 17a+2a+4a-7a-15a-1=10 | | 320=6l+2w | | 2x-(x-3)=-4+3x-17 | | 7x+104=30 |